Opinion on agile methodology in education among the nursing students - Suseela Thiyagarajan; Prakash R. M. Saldanha; Radhakrishnan Govindan; Kunnath Chacko Leena; P Vasuki Prathyusha (Journal of Education and Health Promotion)
BACKGROUND: Agile methodology (AM) is an innovative, active, project-based learning method. The scrum is a popular agile framework widely used in project management and education. This study evaluates the opinions on agile adaptation in nursing curricula among nursing students to identify how AM can be applied in higher education to facilitate learning. MATERIALS AND METHODS: The study employed a cross-sectional design and was conducted at two colleges affiliated with health science university, Bengaluru, India in 2021-22. A 23-item agile scrum perception tool (ASPT) was used to evaluate the opinions on AM among the nursing students after the agile training. The data were analyzed by using IBM SPSS version 28. Descriptive statistics was used to evaluate the opinion. RESULTS: A total of 133 students responded to the questionnaire. Nearly, 99 (74%) of the students strongly agreed the team leader’s (TL) responsibility for managing the time was good. Around 109 (82%) of the students felt that the product owner (PO)/outcome evaluator (OE) explained the course objectives well. About 107 (76%) of students strongly agreed that the learning was facilitated by AM. CONCLUSION: The agile scrum framework (SF) can be taught and fostered to improve collaborative learning, teamwork, leadership abilities, and educational outcomes. The policymakers should set the criteria for implementing agile in the curriculum, and nurse managers should allocate the budget for organizing the training program in the form of workshops and conferences for the nursing educators and nurses which could help to improve the self-directed learning and safe collaborative quality of patient care.